Bakteri yang Berasosiasi dengan Karang Keras yang Terinfeksi Penyakit White Syndrome di Perairan Sawopudo, Sulawesi Tenggara, Indonesia - Ratna Diyah Palupi; Aninditia Sabdaningsih; Diah Ayuningrum; Agus Sabdono (Jurnal Kelautan Tropis, 2025)
Coral disease is one of the most significant factors contributing to coral mortality, leading to a reduction in coral cover. The direct causes of coral disease remain a subject of ongoing investigation by researchers at both national and international levels. There is a relationship between corals and microbes that form the coral holobiont, which can be beneficial, harmful, or neutral. This study aims to isolate, purify, and identify bacteria associated with corals infected with white syndrome (WS) at the molecular level through 16S rRNA gene amplification. Coral samples infected with WS were collected from the Sawopudo Waters in Southeast Sulawesi using purposive sampling through snorkeling. The coral life forms sampled included massive, sub-massive, and branching types, collected from approximately three different colonies. Bacterial analysis associated with WS coral disease was conducted in the laboratory, initially with isolation using the spread plate method and purification through quadrant streaking on peptone, yeast, and agar media. Once pure bacterial colonies were obtained, the bacterial isolates associated with WS-infected corals were injected into healthy corals using laboratory-scale Koch's postulates. The results showed 8 (eight) bacterial isolates associated with WS-infected corals (SWS01, SWS02, SWS03, SWS04, SWS05, SWS06, SWS07, and SWS08). Based on Koch's postulates, isolates SWS01 and SWS07 exhibited visual signs of WS disease. Further isolation and purification were only conducted on isolate SWS01. Molecular identification using 16S rRNA gene amplification revealed that isolate SWS01 is closely related to Priestia flexa (99.72% similarity), isolate SWS07 is closely related to Bacillus velezensis (99.68% similarity), and the re-cultured isolate from Koch's postulates is closely related to Alteromonas macleodii (99.64% similarity).